2021
DOI: 10.1371/journal.pone.0249288
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and expression profiles of circRNAs during abdominal adipose tissue development in Chinese Gushi chickens

Abstract: Circular RNAs (circRNAs) play important roles in adipogenesis. However, studies on circRNA expression profiles associated with the development of abdominal adipose tissue are lacking in chickens. In this study, 12 cDNA libraries were constructed from the abdominal adipose tissue of Chinese domestic Gushi chickens at 6, 14, 22, and 30 weeks. A total of 1,766 circRNAs were identified by Illumina HiSeq 2500 sequencing. These circRNAs were primarily distributed on chr1 through chr10 and sex chromosomes, and 84.95%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 73 publications
1
6
0
Order By: Relevance
“…Therefore, this study predicted the miRNA binding sites on circRNA sequences and found that most of the identified circRNAs had multiple potential miRNA binding sites. These results are consistent with previous studies [ 8 , 16 , 32 ]. This suggests that circRNAs can play a regulatory role in skeletal muscle development by binding to miRNAs.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Therefore, this study predicted the miRNA binding sites on circRNA sequences and found that most of the identified circRNAs had multiple potential miRNA binding sites. These results are consistent with previous studies [ 8 , 16 , 32 ]. This suggests that circRNAs can play a regulatory role in skeletal muscle development by binding to miRNAs.…”
Section: Discussionsupporting
confidence: 94%
“…CircRNA is a newly developed non-coding RNA transcript, which has a unique closed ring structure, which makes circRNAs more stable than linear RNA [ 4 ]. In recent years, due to the rapid development of high-throughput sequencing, thousands of circRNAs have been discovered in various organisms [ 5 , 6 , 7 , 8 ]. CircRNAs are widespread in various tissues and cells of a variety of species [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…As evident, the lncRNA and circRNA expression were tissue- and period-specific [ 31 , 32 ]. Even in the fat tissues, the numbers of lncRNAs and circRNAs identified varied among the different animals, such as 3716 lncRNAs [ 33 ] and 5141 circRNAs [ 34 ] identified in the subcutaneous fat of cattle, 9082 identified lncRNAs identified in the tail fat of sheep [ 35 ], and 1637 circRNAs identified in the chicken abdominal fat [ 36 ]. Coincidently, similar numbers of lncRNAs were identified in the broiler abdominal fat, but our study identified fewer numbers of circRNAs in the abdominal fat of 7 wks broilers than that in the other animals, possibly related to the various fat samples, species, and development stage.…”
Section: Discussionmentioning
confidence: 99%
“…proposed that the ciR-PTPN23-miR-15a-E2F3 axis is involved in the inhibition of H2S-induced cell proliferation and apoptosis in chickens ( Hu et al, 2021 ). CircRNAs regulated lipid metabolism and adipocyte proliferation and differentiation during chicken abdominal adipose tissue development through complex ceRNA networks ( Jin et al, 2021 ). circ-PLXNA1 played a role in duck adipocyte differentiation through circRNA expression profiling ( Wang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%